Ochrona informacji poufnych pracodawcy w świetle dyrektywy nr 2016/943/UE z 8 czerwca 2016 roku: [Occupational aspects of Directive (EU) 2016/943 OF 8 June 2016] (Studia Prawnicze / The Legal Studies, 2017)
Przedsiębiorstwa wykorzystują poufność jako narzędzie zarządzania konkurencyjnością i innowacjami w działalności badawczej. Poufność można również odnieść do szerokiej gamy informacji, wykraczających poza wiedzę techniczną i dane handlowe, takich jak informacje dotyczące klientów i dostawców, biznesplany oraz badania i strategie rynkowe. Innowacyjne przedsiębiorstwa są w coraz większym stopniu narażone na nieuczciwe praktyki – zarówno wewnątrz Unii, jak i poza nią – mające na celu przywłaszczenie tajemnic przedsiębiorstwa, takie jak np. kradzieże, oszustwa, nieuprawnione kopiowanie, szpiegostwo go-spodarcze czy naruszenie wymogów poufności. Ostatnie zmiany, takie jak globalizacja, outsourcing, dłuższe łańcuchy dostaw oraz coraz bardziej powszechne wykorzystywanie technologii informacyjno-komunikacyjnych, przyczyniają się do zwiększenia ryzyka występowania tego rodzaju praktyk. The regulations of new Directive (EU) 2016/943 of 8 June 2016 on the protection of undisclosed know-how and business information (trade secrets) against their unlawful acquisition, use and disclosure provide employers as the holders of trade secrets with a higher level of legal protection. Employers will have protective measures against the disclosure of employer's secrets at their disposal, which are laid down in Labour Code and in Unfair Competition Act. This Directive stipulates that data constituting the trade secret are not widely known or easily accessible to people who work in a given trade and process this type of information on a daily basis. This secret may constitute every confidential piece of information that the employer considers to have any, even potential, commercial value. However, the domestic law still does not provide a sufficient level of protection of employers-whistle blowers, that is people who inform about irregularities in the company. Therefore, the introduction of special legal protection of whistle blowers will be an absolute innovation. To that end, the legislator should state in the labour law the boundaries of protection of whistle blowers who act in good faith, having regard to public interest protection and employer’s interests.